1990
DOI: 10.1084/jem.171.4.1171
|View full text |Cite
|
Sign up to set email alerts
|

Further analysis of the T cell receptor gamma/delta+ peripheral lymphocyte subset. The V delta 1 gene segment is expressed with either C alpha or C delta.

Abstract: In the present study, we have characterized the reactivity of two mAbs that are directed at the human TCR-gamma/delta. These reagents, designated anti-A13 and anti-TiV delta 2, were found to recognize antigenic determinants encoded by the TCR V delta 1 and V delta 2 gene segments, respectively. Immunofluorescence analyses performed with the antibodies confirmed that, in the TCR-gamma/delta+ cell subpopulation, the expression of V delta 2+ delta chains is largely predominant, as compared with the V delta 1+ cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(30 citation statements)
references
References 40 publications
(66 reference statements)
2
28
0
Order By: Relevance
“…2). This result confirmed the previous findings by Miossec et al [6,7] that a small subset ( X 0.5%) of human peripheral T cells expressed Vˇ1-encoded variable segments on § g T cells. Using a C gspecific antisense primer, we isolated TCR-g cDNA containing a V g 13.3-encoded gene segment (Table 1), suggesting that the Vˇ1.1-bearing TCR- § chain was paired with TCR-g chain on the surface of CTL 55.…”
Section: Analysis Of Tcr-encoding Genes Of Ctl 55supporting
confidence: 82%
See 2 more Smart Citations
“…2). This result confirmed the previous findings by Miossec et al [6,7] that a small subset ( X 0.5%) of human peripheral T cells expressed Vˇ1-encoded variable segments on § g T cells. Using a C gspecific antisense primer, we isolated TCR-g cDNA containing a V g 13.3-encoded gene segment (Table 1), suggesting that the Vˇ1.1-bearing TCR- § chain was paired with TCR-g chain on the surface of CTL 55.…”
Section: Analysis Of Tcr-encoding Genes Of Ctl 55supporting
confidence: 82%
“…3). In addition, mAb A13 [9], specific for an epitope encoded by Vˇ1 gene segments transcribed along with either J § C § or JˇCˇ [6] reacted with CTL 55 (Fig. 3A).…”
Section: Flow-cytometric Analysis Of Ctl 55 and Peripheral Lymphocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thick bars indicate two or three V genes sharing an identical similarity value. Asterisks correspond to V genes expressed or rearranged at both TCRD and TCRA loci but without a double nomenclature (for DV1, see Miossec et al 1990) Here we show that the same, small set of V genes is rearranged both in the productive and unproductive allele. Ten of the twelve V gene rearrangements found on the unproductive chromosome contained the four most common DVelements (DV1-3 and DVS), which were expressed on the surface of over 95% (77/80) of our TCRG/D clones.…”
Section: Discussionmentioning
confidence: 77%
“…ADV segments, however, isolated using V segment-specific PCR primers, may be rare transcripts, expressed in (z[3 T cells in which the TCRD locus is not deleted on one allele (Genev6e et al 1994). It has been reported only for the DVIO1 gene segment that its product can be expressed on the surface of both the o~3 and 76 T-cell subpopulations (Miossec et al 1990). It has recently been shown that y8 Tcell clones express two novel DV gene segments, called V67 and V68, on the cell surface.…”
Section: The O~ and 8 Familiesmentioning
confidence: 99%